Membongkar Hegemoni Tafsir : Konsep "Zauj" sebagai Landasan Kesetaraan Gender dalam Al-Qur'an - Nurul Fathanah Alfikriah; Achmad Abubakar; Muhsin Mahfudz (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The issue of gender equality in Qur'anic interpretation remains a profound problem, particularly when biased lexical interpretations obscure the liberating theological principles of the text. This article aims to analyze the concept of "zauj" in the Qur'an and its relevance as a foundation for gender equality. This research employs a qualitative approach, utilizing Toshihiko Izutsu's semantic analysis method and contemporary Qur'anic hermeneutics. The findings reveal that "zauj" is a cosmological principle of paired creation, implying equality, compatibility, and reciprocity. The reduction of the meaning of "zauj" to merely "wife" in many traditional interpretations constitutes a semantic distortion that perpetuates gender inequality. The gender-based relational disparities that occur are more due to patriarchal interpretive structures than the universal message of the Qur'an itself. The concept of "zauj" instead offers a paradigm of equal and complementary relations, which can form the basis for reconstructing gender-just family ethics in Islam. Therefore, the deconstruction of interpretive hegemony and the holistic reconstruction of the meaning of "zauj" are essential prerequisites for realizing egalitarian and just gender relations in Islam.